Predicting Black Parents’ Attitudes Toward Corporal Punishment: A Moderated-Mediation Model of Frequency and Valence of Childhood Experiences - Duong, Hue Trong (Journal of interpersonal violence, 2024)
Child corporal punishment (CP) may lead to child physical abuse, which is a public health concern in the United States. The present study examined major risk factors predicting attitudes toward CP among a sample of Black parents (N = 394), including frequency and valence of experiences of CP during childhood, outcome expectancies of CP, and perceptions of self-efficacy and response efficacy of non-physical discipline strategies. Structural equation modeling results revealed that the indirect associations between CP frequency and attitudes through self-efficacy and response efficacy were moderated by CP valence. Results extend the literature and point to the need for incorporating information about efficacy of evidence-based non-physical discipline strategies into intervention messages targeting prevention of child physical abuse.